Enhancing Public Legal Awareness of the Dangers of Normalizing Incest Fantasies on the Internet as an Effort to Protect Children within the Family of Banyumanik Semarang - Ida Musofiana; Noor Lailatul Izza; Rizki Adi Pinandito (LP2M of Institute for Research and Community Services - UIN Walisongo, 2026)
The increasing circulation of digital content that normalizes incest fantasies poses a challenge to child protection within families. This community service program was conducted in Banyumanik Subdistrict, Semarang City, where preliminary assessments indicated high internet access, limited parental digital supervision, and low public awareness of the legal risks associated with incest-related content. The program aimed to strengthen legal awareness and digital literacy to prevent children's exposure to harmful online content. Using a Participatory Community Education approach, the program involved 35 participants through legal counselling, digital literacy training, focus group discussions, and pre-test/post-test evaluations. Before the intervention, 78% of participants were unaware that incest-fantasy content is categorized as prohibited pornography under Indonesian law. Following the program, 89% of participants were able to identify forms of digital content that normalize incest fantasies, indicating a 67 percentage-point improvement in legal awareness and digital literacy. The program demonstrates that community-based legal education can strengthen family resilience and support child protection in the digital environment.